The moderating effect of community participation on telecentre value creation - Md Dahalin, Zulkhairi; Othman, Nafishah; Mat Aji, Zahurin; Md Yusop, Nor Iadah (2016)
This paper examines community participation in using ICT in rural area telecentres with the aim to understand its effect on the relationship between diffusion and adoption of the telecentre on socio-economic value creation.Active community participation is a major factor in contributing to sustainability of telecentres.However,understanding the moderating role of community participation on the effect of diffusion and adoption of the telecentre on value creation is equally important in order to bridge the digital divide.To enable this, a survey was conducted among communities in the rural areas in the northern states of Malaysia.The aim was to determine whether the effect of diffusion and adoption on value creation depends on the community actively participates in the use of the telecentre.The results show that community participation moderates the effect of both diffusion and adoption on value creation with tendency of non-user having negative impact on adoption which can adversely affect value creation.This study found that non-users should be encouraged to use the telecentre facilities in order to bridge the digital divide and increase the socio-economic value of the community.